2019
DOI: 10.13057/biodiv/d201126
|View full text |Cite
|
Sign up to set email alerts
|

Population of phosphate solubilizing bacteria in the liquid organic fertilizer created from palm oil bunches and pineapple rhizome

Abstract: Abstract. Dermiyati, Suharjo R, Telaumbanua M, Ilmiasari Y, Yosita R, Annisa RM, Sari AW, Andayani AP, Yulianti DM. 2019. Population of phosphate solubilizing bacteria in the liquid organic fertilizer created from palm oil bunches and pineapple rhizome. Biodiversitas 20: 3315-3321. Palm oil bunches and pineapple rhizomes are abundant in Indonesia, especially in Lampung Province due to widespread agro-industrial company and they are potential to be used as sources for liquid organic fertilizer. This study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Local Microorganism solution was developed using oil palm empty fruit bunches in three conditions, namely aerobic, anaerobic, and facultative anaerobic as described by Dermiyati et al (2019). Making a suspension of local microorganisms was done by mixing 2.5 kg of finely chopped oil palm empty fruit bunches, 0.5 kg brown sugar, 2.5 L rice washing water, and 2.5 L coconut water, then put into the reactor machine and each fermentation condition contains the same ingredients.…”
Section: Development Of Local Microorganism Solutions From Oil Palm Ementioning
confidence: 99%
“…Local Microorganism solution was developed using oil palm empty fruit bunches in three conditions, namely aerobic, anaerobic, and facultative anaerobic as described by Dermiyati et al (2019). Making a suspension of local microorganisms was done by mixing 2.5 kg of finely chopped oil palm empty fruit bunches, 0.5 kg brown sugar, 2.5 L rice washing water, and 2.5 L coconut water, then put into the reactor machine and each fermentation condition contains the same ingredients.…”
Section: Development Of Local Microorganism Solutions From Oil Palm Ementioning
confidence: 99%
“…This is because there are 791 bacterial isolates in liquid organic fertilizer with pineapple ingredients. These isolates can degrade and dissolve nutrients such as nitrogen, phosphate, and potassium [39]. Soil microbial communities can affect the decomposition of organic matter and nutrient cycles to improve soil aggregation and further support plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Suspension of plant extracts from pineapple rhizomes gave the highest phosphate solubilization index compared to suspensions of plant extracts from banana weevil and EFB. Dermiyati et al (2019) reported that seven bacterial isolates derived from suspensions of plant extracts from EFB and four bacterial isolates from pineapple rhizomes had a very high ability to dissolve phosphate but bacterial isolates from suspensions from pineapple rhizomes had a higher phosphate solubilization index. They were compared to the suspension from EFB.…”
Section: Discussionmentioning
confidence: 99%
“…Oil palm empty fruit bunches (EFB), pineapple rhizomes, and banana weevil contain macro and micronutrients, microbial decomposers, and growth regulators needed by plants. The results of the study by Dermiyati et al (2019;2020a) showed that pineapple rhizome and EFB waste contained microorganisms with various characteristics. Lestari et al (2019) also reported that suspension of plant extracts from banana weevil could increase onion growth and production depending on the frequency of application.…”
Section: Introductionmentioning
confidence: 99%